A new species of Creagrutus (Characidae: Stevardiinae) from the upper Rió Magdalena, Colombia - Albornoz-Garzon, Juan G.; Conde-Saldana, Cristhian C. [UNESP]; Garcia-Melo, Jorge E.; Taphorn, Donald C.; Villa-Navarro, Francisco A. (Magnolia Press, 2018)
A new species of Creagrutus is described from several localities in the upper Rió Magdalena drainage, Colombia. Creagrutus dulima n. sp. differs from all trans-Andean congeners by the combination of a relatively small orbital diameter, the shape and position of hooks on the pelvic-fin rays, in having the third infraorbital not in contact with the preopercle ventrally, and the presence of a dark, reticulated pigmentation pattern on the dorsal portion of body. The distribution of Creagrutus species in the Magdalena-Cauca River Basin is discussed, and an updated identification key for species of trans-Andean Creagrutus is provided.
Keywords: Characiformes; Ostariophysi; Taxonomy; Trans-Andean region